Oral Soft-Tissue Angiolipoma: Rarest Intraoral Lipomatous Lesion - Ankita Giri; Ravleen Nagi; Manish Kumar; Stuti Shukla (Journal of Integrated Health Sciences)
Intraoral angiolipoma (AL) is a rare clinical and histological variant of lipoma consisting of predominantly proliferating vascular channels interspersed with mature fat cells. The exact etiopathogenesis of this neoplasm still has to be established, and it clinically presents intraorally as a well-circumscribed, asymptomatic, or tender submucosal nodular mass that requires complete surgical excision. This report describes a rare case of AL located in the upper lip of a 65-year-old male patient and also focuses on its clinical and histological characteristic features for accurate diagnosis and better management.